An antibacterial graphene sponge material / Zr-Bi 2 S 3 Preparation process
The preparation of three-dimensional graphene sponge/Zr-Bi2S3 antibacterial materials by one-step solvothermal method solves the problems of complex and high cost of existing antibacterial agents, and achieves efficient antibacterial effects and simplified process flow.
Patent Information
- Application Number
- CN202410673652.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-05-28
AI Technical Summary
The reaction process of existing antibacterial agents is cumbersome and takes a long time, nanosilver is expensive, and the product stability is poor, which limits its practical application.
Using a one-step solvothermal method, graphene oxide is treated with zirconium salt, bismuth salt and sulfur sources by ultrasonic mixing. After adding ethanolamine, it reacts at 180-200°C to form a three-dimensional graphene sponge/Zr-Bi2S3 antibacterial material.
The prepared antibacterial materials have excellent antibacterial properties and can effectively kill Staphylococcus aureus and E. coli. The process is simple and suitable for a variety of application fields.
Smart Images

Figure CN118637661B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antibacterial materials, and in particular to a preparation process of an antibacterial graphene sponge material / Zr-Bi2S3. Background Art
[0002] With the development of science and technology, the types of bacteria are gradually increasing, which seriously threatens human health. At present, a large number of antibiotics are widely used for sterilization treatment. However, the extensive use of antibiotics has caused bacteria to develop drug resistance. With the increasing number of drug-resistant bacteria, traditional antibiotics and drug treatments cannot effectively kill bacteria. At present, drug-resistant bacteria have caused a serious threat to human health. Drug-resistant bacteria have become a health problem that humans urgently need to solve. Therefore, exploring a new and effective antibacterial substance has extremely important research value.
[0003] In recent years, the research on non-antibiotic antibacterial substances has become a research hotspot and focus, among which antibacterial nanomaterials have attracted widespread attention. Antibacterial nanomaterials can overcome the problem of bacterial resistance and have broad practical application prospects. As a new type of two-dimensional nanomaterial, graphene has the characteristics of lightness, high strength, and strong conductivity. At the same time, graphene also exhibits excellent antibacterial and antibacterial capabilities. According to scientific research, graphene can have certain antibacterial and antibacterial effects on a variety of microorganisms such as bacteria, fungi and viruses. Compared with traditional chemical antibiotics, graphene is renewable, easier to obtain, cheaper, and has almost no bacterial resistance. At present, scientists are exploring the application research of graphene antibacterial and antibacterial.
[0004] Patent CN117413844A discloses a graphene oxide / nanosilver antibacterial agent, which firstly chlorinates graphene oxide with SOCl2, then uses the reaction product of diamine and ferrocene formaldehyde to react the aminated ferrocenyl Schiff base with the chlorinated graphene oxide to obtain ferrocenyl Schiff base-modified graphene oxide, and finally uses a chemical reduction method to in-situ generate nanosilver on the surface of the ferrocenyl Schiff base-modified graphene oxide to obtain a graphene oxide / nanosilver composite antibacterial agent, which has long-lasting and stable antibacterial properties. However, the reaction process of the antibacterial agent is cumbersome and time-consuming, and the nanosilver is expensive, which limits its practical application. Patent CN116695424A discloses dissolving graphene oxide in N-methylimidazole hydrogen sulfate ionic liquid, adding nano-carboxyl chitosan dispersion under ultrasonic action to react with graphene oxide sheets to obtain graphene oxide / nano-carboxyl chitosan complex, and then subjecting the graphene oxide / nano-carboxyl chitosan complex to in-situ grafting reaction with fabric in N-methylimidazole hydrogen sulfate ionic liquid by microwave radiation to obtain graphene oxide / nano-carboxyl chitosan in-situ grafted fabric. However, the product yield is low and the stability is poor. Patent CN116891231A discloses the use of polyaniline (PANI) and tetrabutyl titanate precursor hydrothermal reaction to prepare anatase nano-TiO2, nano-TiO2 microparticles and organic molecular additives are subjected to ultrasonic chemical reaction to cross-link into modified TiO2 nanoparticles, firstly the modified nano-TiO2 microparticles are formed by cross-linking reaction of the hydrophilic ends of nano-TiO2 and organic molecular additives, and then the positively charged nano-TiO2 is combined with the edge of the graphene oxide sheet, however, there is still a certain agglomeration in the dioxide state, resulting in the inability to fully exert the antibacterial properties. Summary of the invention
[0005] In order to overcome the technical defects of the above-mentioned prior art, the purpose of the present invention is to provide a preparation process of antibacterial graphene sponge material / Zr-Bi2S3 to solve the threats posed by various bacterial infections, especially infections caused by drug-resistant bacteria, to human life.
[0006] A graphene sponge / Zr-Bi2S3 antibacterial material, the preparation process of which comprises the following steps:
[0007] Step 1, adding graphene oxide GO into a mixed solvent of ethylene glycol / glycerol, and subjecting to ultrasonic mixing to obtain solution a;
[0008] Step 2, dissolving zirconium salt, bismuth salt and sulfur source in solution a obtained in step 1, and subjecting to ultrasonic mixing to obtain a mixed solution b;
[0009] Step 3, adding ethanolamine dropwise into the mixed solvent in step 2, and continuing ultrasonic mixing treatment to obtain a mixed solution c;
[0010] Step 4: Transfer the mixed solution c in step 3 to a reactor, react at 180-200°C for 18-24 hours. After the reaction is completed, cool naturally, centrifuge, wash it with deionized water and anhydrous ethanol 2-5 times, and then vacuum freeze-dry to obtain the product three-dimensional graphene sponge / Zr-Bi2S3 antibacterial material.
[0011] Specifically, the zirconium source is zirconium nitrate;
[0012] Specifically, the bismuth source is bismuth nitrate;
[0013] Specifically, the sulfur source is thioacetamide;
[0014] Specifically, the molar ratio of zirconium nitrate, bismuth nitrate, thioacetamide, and ethanolamine is (0.02-0.1):2:3:(1-2);
[0015] Specifically, the volume ratio of ethylene glycol to glycerol in the ethylene glycol / glycerol mixed solvent is (2-4):1;
[0016] Specifically, the ultrasonic power of the ultrasonic treatment in step 1 is selected to be 100-150w;
[0017] Specifically, the ultrasonic power of the ultrasonic treatment in step 2-3 is selected to be 50-80w;
[0018] Specifically, the vacuum freeze drying temperature is -10 to -40°C, and the vacuum freeze drying time is 10 to 20 hours;
[0019] Specifically, the antibacterial material of three-dimensional graphene sponge / Zr-Bi2S3, wherein the Zr-doped Bi2S3 is in a nanowire structure and is composited with the three-dimensional graphene sponge;
[0020] The technical effects achieved by the present invention are:
[0021] Ethylene glycol / glycerol was used as the reaction solvent, and ethanolamine was added during the solvothermal process to prepare three-dimensional graphene / Zr-Bi2S3 with excellent antibacterial properties. The nanowire Zr-Bi2S3 has a weaving characteristic and is interspersed in the three-dimensional graphene network, which effectively improves the integrity and stability of the three-dimensional structure. On the one hand, the graphene sheets can cover cells to prevent bacterial proliferation. On the other hand, the graphene sheets generated by solvothermal reaction belong to a weak reduction reaction, and their surface still contains certain surface defects such as oxygen-containing functional groups. It has a certain oxidation activity, thereby improving the antibacterial property. In addition, the three-dimensional graphene sponge with a hierarchical pore structure has a strong adsorption capacity, which can wrap the ion-gas exchange position of bacteria, so that the bacteria are isolated and cannot continue to reproduce; the three-dimensional graphene network structure avoids the agglomeration and stacking of nanowire Zr-Bi2S3, improves its dispersibility and specific surface area, and thus effectively improves its antibacterial property.
[0022] By doping Bi2S3 with Zr, the recombination of photogenerated carriers can be effectively reduced and the light response range can be increased, thereby improving the photocatalytic efficiency.
[0023] The three-dimensional graphene / Zr-Bi2S3 antibacterial agent prepared by the present invention adopts a one-step solvothermal method, has a simple preparation process, has a strong killing effect on Staphylococcus aureus and Escherichia coli, and can be applied to many fields such as building materials, office supplies, coatings, toys, and medical treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope photograph of the graphene sponge / Zr-Bi2S3 of the present invention. DETAILED DESCRIPTION
[0025] Example 1
[0026] Step 1, adding 50 mg of graphene oxide GO into a 65 ml mixed solvent of ethylene glycol / glycerol, wherein the volume ratio of ethylene glycol to glycerol in the mixed solvent is 2:1, and mixing with 100 W power ultrasound for 30 min to obtain solution a;
[0027] Step 2: dissolving zirconium nitrate, bismuth nitrate and thioacetamide in the solution a obtained in step 1, and subjecting the mixture to ultrasonic mixing at 50W for 15min to obtain a mixed solution b.
[0028] Step 3, dropwise adding ethanolamine into the mixed solvent in step 2, and continue 50W ultrasonic mixing treatment for 15 minutes to obtain a mixed solution c; wherein the added amounts of zirconium nitrate, bismuth nitrate, thioacetamide, and ethanolamine are 0.05mmol, 2mmol, 3mmol, and 2mmol, respectively;
[0029] Step 4: Transfer the mixed solution c in step 3 to a 100 ml reactor, react at 180°C for 18 hours. After the reaction is completed, cool naturally, centrifuge, wash it with deionized water and anhydrous ethanol for 3 times, and then freeze-dry it in vacuum at a temperature of -10°C for 10 hours. Obtain the product graphene sponge / Zr-Bi2S3 antibacterial material.
[0030] Example 2
[0031] Step 1, adding 30 mg of graphene oxide GO into a 65 ml mixed solvent of ethylene glycol / glycerol, wherein the volume ratio of ethylene glycol to glycerol in the mixed solvent is 2:1, and mixing with 100 W power ultrasound for 30 min to obtain solution a;
[0032] Step 2: dissolving zirconium nitrate, bismuth nitrate and thioacetamide in the solution a obtained in step 1, and subjecting the mixture to ultrasonic mixing at 50W for 15min to obtain a mixed solution b.
[0033] Step 3, dropwise adding ethanolamine into the mixed solvent in step 2, and continue 50W ultrasonic mixing for 15 minutes to obtain a mixed solution c; the addition amounts of zirconium nitrate, bismuth nitrate, thioacetamide, and ethanolamine are selected to be 0.05mmol, 2mmol, 3mmol, and 2mmol;
[0034] Step 4: Transfer the mixed solution c in step 3 to a 100 ml reactor, react at 180°C for 18 hours. After the reaction is completed, cool naturally, centrifuge, wash it with deionized water and anhydrous ethanol for 3 times, and then freeze-dry it in vacuum at a temperature of -10°C for 10 hours. Obtain the product graphene sponge / Zr-Bi2S3 antibacterial material.
[0035] Example 3
[0036] Step 1, adding 50 mg of graphene oxide GO into 80 ml of a mixed solvent of ethylene glycol / glycerol, wherein the volume ratio of ethylene glycol to glycerol is 3:1, and mixing with 100 W power ultrasound for 30 min to obtain solution a;
[0037] Step 2: dissolving zirconium nitrate, bismuth nitrate and thioacetamide in the solution a obtained in step 1, and subjecting the mixture to ultrasonic mixing at 50W for 15min to obtain a mixed solution b.
[0038] Step 3, dropwise adding ethanolamine into the mixed solvent in step 2, and continue 50W ultrasonic mixing treatment for 15 minutes to obtain a mixed solution c; wherein the added amounts of zirconium nitrate, bismuth nitrate, thioacetamide, and ethanolamine are 0.05mmol:2mmol:3mmol:2mmol;
[0039] Step 4: Transfer the mixed solution c in step 3 to a 100 ml reactor, react at 200°C for 18 hours. After the reaction is completed, cool naturally, centrifuge, wash it with deionized water and anhydrous ethanol for 3 times, and then freeze-dry it in vacuum at a temperature of -10°C for 10 hours. Obtain the product graphene sponge / Zr-Bi2S3 antibacterial material.
[0040] Comparative Example 1
[0041] Step 1, adding 50 mg of graphene oxide GO into a 65 ml mixed solvent of ethylene glycol / glycerol, wherein the volume ratio of ethylene glycol to glycerol is 2:1, and mixing with 100 W power ultrasound for 30 min to obtain solution a;
[0042] Step 2: dissolving bismuth nitrate and thioacetamide in the solution a obtained in step 1, and subjecting the mixture to ultrasonic mixing at 50W for 15min to obtain a mixed solution b.
[0043] Step 3, dropwise adding ethanolamine into the mixed solvent in step 2, and continue 50W ultrasonic mixing treatment for 15 minutes to obtain a mixed solution c; wherein bismuth nitrate, thioacetamide, and ethanolamine are selected to be 2mmol, 3mmol, and 2mmol;
[0044] Step 4: Transfer the mixed solution c in step 3 to a 100 ml reactor, react at 180°C for 18 hours. After the reaction is completed, cool naturally, centrifuge, wash it with deionized water and anhydrous ethanol for 3 times, and then vacuum freeze-dry. The vacuum freeze-drying temperature is -10°C and the vacuum freeze-drying time is 10 hours. The product graphene sponge / Bi2S3 antibacterial material is obtained.
[0045] Comparative Example 2
[0046] Step 1, preparing a 65 ml volume of a mixed solvent of ethylene glycol / glycerol as solution a, wherein the volume ratio of ethylene glycol to glycerol in the mixed solvent is 2:1;
[0047] Step 2: dissolving zirconium nitrate, bismuth nitrate and thioacetamide in the solution a obtained in step 1, and subjecting the mixture to ultrasonic mixing at 50W for 15min to obtain a mixed solution b.
[0048] Step 3, dropwise adding ethanolamine into the mixed solvent in step 2, and continue 50W ultrasonic mixing treatment for 15 minutes to obtain a mixed solution c; wherein the molar ratio of zirconium nitrate, bismuth nitrate, thioacetamide, and ethanolamine is 0.05mmol:2mmol:3mmol:2mmol;
[0049] Step 4: Transfer the mixed solution c in step 3 to a 100 ml reactor, react at 180°C for 18 hours. After the reaction is completed, cool naturally, centrifuge, wash it with deionized water and anhydrous ethanol for 3 times, and then vacuum freeze-dry. The vacuum freeze-drying temperature is -10°C and the vacuum freeze-drying time is 10 hours. The product Zr-Bi2S3 antibacterial material is obtained.
[0050] Comparative Example 3
[0051] Step 1, adding 50 mg of graphene oxide GO to a 65 ml mixed solvent of ethylene glycol / glycerol, wherein the volume ratio of ethylene glycol to glycerol in the mixed solvent is 2:1, and mixing treatment is performed at 100 W power ultrasound for 30 min to obtain solution a; transferring the evenly mixed solution to a 100 ml reactor, reacting at 180 ° C, maintaining for 18 hours, and after the reaction is completed, naturally cooling and centrifuging, washing it with deionized water and anhydrous ethanol for 3 times, and then vacuum freeze drying, the vacuum freeze drying temperature is -10 ° C, and the vacuum freeze drying time is 10 hours; obtaining the product graphene sponge material.
[0052] Antibacterial performance test:
[0053] Staphylococcus aureus was used as the bacterial species for antibacterial testing. 1 mg of the photocatalytic bactericidal materials of Examples 1-3 and Comparative Examples 1-3 were placed in a concentration of 2×10 5 CFU / mL of Staphylococcus aureus solution was diluted 100 times and 200 μL of the solution was taken in a culture dish, 30 ml of nutrient agar was added to the culture dish, and the culture dish was placed in a 37°C incubator for 24 hours. The antibacterial rate of the antibacterial materials of the embodiments and comparative examples under dark and light conditions was calculated by colony counting method.
[0054] Antibacterial rate (dark) Antibacterial rate (light) Example 1 87% 98% Example 2 83% 99% Example 3 79% 99% Comparative Example 1 77% 86% Comparative Example 2 21% 81% Comparative Example 3 69% 73%
[0055] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.
Claims
1. A preparation process of antibacterial graphene sponge / Zr-Bi2S3 material, characterized in that: The preparation process includes the following steps: Step 1, adding graphene oxide GO into a mixed solvent of ethylene glycol / glycerol, and subjecting to ultrasonic mixing to obtain solution a; Step 2, dissolving zirconium salt, bismuth salt and sulfur source in solution a obtained in step 1, and subjecting to ultrasonic mixing to obtain a mixed solution b; Step 3, adding ethanolamine dropwise into the mixed solvent in step 2, and continuing ultrasonic mixing treatment to obtain a mixed solution c; Step 4: Transfer the mixed solution c in step 3 to a reactor, react at 180-200°C for 18-24 hours. After the reaction is completed, cool naturally, centrifuge, wash it with deionized water and anhydrous ethanol 2-5 times, and then freeze-dry it in vacuum to obtain the product graphene sponge / Zr-Bi2S3 material.
2. According to the preparation process of the antibacterial graphene sponge / Zr-Bi2S3 material according to claim 1, the zirconium source is zirconium nitrate.
3. According to the preparation process of the antibacterial graphene sponge / Zr-Bi2S3 material according to claim 2, the bismuth source is bismuth nitrate.
4. According to the preparation process of the antibacterial graphene sponge / Zr-Bi2S3 material according to claim 3, the sulfur source is thioacetamide.
5. According to the preparation process of the antibacterial graphene sponge / Zr-Bi2S3 material described in claim 4, the molar ratio of bismuth nitrate to thioacetamide is 2:3; the molar ratio of zirconium nitrate to bismuth nitrate is (0.01-0.05):1; the molar ratio of bismuth nitrate to ethanolamine is 1:(0.5-1).
6. According to the preparation process of an antibacterial graphene sponge / Zr-Bi2S3 material according to claim 1, the volume ratio of ethylene glycol to glycerol in the mixed solvent of ethylene glycol / glycerol is (2-4):
1.
7. According to the preparation process of an antibacterial graphene sponge / Zr-Bi2S3 material according to claim 1, the ultrasonic power of the ultrasonic treatment in step 1 is selected to be 100-150w.
8. According to the preparation process of an antibacterial graphene sponge / Zr-Bi2S3 material according to claim 1, the ultrasonic power of the ultrasonic treatment in steps 2 and 3 is selected to be 50-80w.
9. According to the preparation process of the antibacterial graphene sponge / Zr-Bi2S3 material described in claim 1, the vacuum freeze-drying temperature is -10 to -40°C, and the vacuum freeze-drying time is 10-20 hours.
10. According to the preparation process of the antibacterial graphene sponge / Zr-Bi2S3 material as described in claim 1, Zr-Bi2S3 is in a nanowire structure and is compounded with a three-dimensional graphene sponge.
Citation Information
Patent Citations
Graphene oxide / nano carboxyl chitosan in-situ grafted fabric and preparation method thereof
CN116695424A
Preparation method of graphene oxide / titanium dioxide composite nanomaterial
CN116891231A
Sea-urchin-shaped bismuth sulfide / macropore graphene composite material, preparation method and application thereof
CN107026263A
Bi2S3-MoS2 / graphene composite nano material and preparation method thereof
CN110247038A